DESAIN STASIUN RADIO YANG ERGONOMIS: SOLUSI UNTUK KENYAMANAN DAN EFISIENSI OPERATOR RADIO AMATIR LOKAL KOTA MATARAM - Wiryajati, I Ketut; Putra, I Ketut Perdana; Joniarta, I Wayan; Maryati, Sri; Adnyani, Ida Ayu Sri; Citarsa, Ida Bagus Fery; Supriono, Supriono (Jurusan Teknik Elektro Universitas Mataram, 2025)
The Indonesian Amateur Radio Organization (ORARI) plays a crucial role in emergency communication and the development of amateur radio technology. However, a lack of attention to ergonomics in radio station design can lead to health issues and decreased operator efficiency. This study highlights the application of ergonomic principles in amateur radio stations to improve the comfort and efficiency of ORARI operators. Through a participatory approach, observations, questionnaires, and training were conducted on ergonomic sitting posture, optimal equipment arrangement, appropriate lighting, and workplace environmental factors. Evaluation results indicate that ergonomic implementation reduced back pain complaints by 33%, neck strain by 35%, and eye fatigue by 32%. Additionally, operator efficiency increased by up to 25% after ergonomic adjustments. Workstation modifications, including the selection of ergonomic chairs, optimal equipment placement, and proper lighting, contributed to enhanced comfort and productivity. This study confirms that applying ergonomic principles not only benefits the physical health of operators but also improves job satisfaction and communication effectiveness. These recommendations are expected to serve as a reference for ORARI in creating a healthier and more efficient working environment for its members.